'Mandela's out so apartheid has finished': the British Anti-Apartheid Movement and South Africa's transition to majority rule, 1990-1994. Issue 3 (3rd July 2022) - Graham, Matthew; Fevre, Christopher
ABSTRACT: Based on original archival research and oral history interviews, this article examines how the British Anti-Apartheid Movement (AAM) adapted to the evolving circumstances during South Africa's transition from apartheid to democracy between 1990 and 1994. It argues that the successful framing and impact of the Free Nelson Mandela Campaign (FNMC) of the 1980s, inadvertently created a series of challenges for the AAM in the years after Mandela's release from prison in February 1990, as many in Britain came to associate this moment with the end of apartheid. The pervasive sense that apartheid was over, coupled with the complexity, uncertainty and violence of South Africa's political transition, created a difficult campaigning environment for the AAM, who found it hard to maintain the momentum generated through the FNMC. Despite encountering numerous (trans)national and local challenges which inhibited its impact after 1990, this article concludes that the AAM's persistent campaigning presence allowed it to capitalise following renewed British interest in South Africa following the announcement in June 1993 of a date for the first non-racial democratic election. This enabled the AAM to make a tangible contribution, primarily through fundraising, to the African National Congress' successful election victory in May 1994.